Penerapan Pidana Penjara terhadap Kleptomaniak: Studi Kasus Putusan Pengadilan - Syarif Saddam Rivanie; Slamet Sampurno Soewondo; Nur Azisa; Muhammad Topan Abadi; Ismail Iskandar (CV. Social Politic Genius (SIGn), 2022)
This study aims to examine and analyze the Judge’s application of imprisonment to kleptomaniacs based on Decision No. 574/Pid.B/2019/PN.Dps. This study uses a normative juridical research method. The data was collected using literature study techniques on primary, secondary, and tertiary legal materials. The collected legal material is then analyzed using qualitative data analysis methods with a statute approach and a case approach which will then conclude the object of the research. The results show that the Judge’s application of imprisonment to the accused is based on Decision No. 574/Pid.B/2019/PN.Dps was the right decision. In this case, the problem of kleptomania currently ongoing in court should be proven with a Psychiatric Visum et Repertum. While the Letter of Statement No. 01/II.MR/RSPI/2019 cannot be the basis for the implementation of eliminating punishment. To determine that a person has kleptomania must undergo a process of examination for a minimum of two weeks to three months. Therefore, it is recommended that investigators provide the opportunity or take the initiative to prove the suspect’s mental condition before being processed to the following legal proof stage. So no more accused who prove their status as kleptomaniacs using the letter of statement. The Judge is also recommended to decide by giving measures sanction to the accused if proven to have kleptomania to avoid the recurrence of the crime of theft in the future.